In situ determination of polysulfides in alkaline hydrogen sulfide solutions. (10th August 2019) - Bedoya-Lora, Franky E.; Hankin, Anna; Kelsall, Geoff H.
Abstract: A method was developed to determine low concentrations of polysulfide ions (Sn 2− expressed as zero-valent sulfur) in situ and in the presence of high concentrations (0.5 mol dm −3 ) of hydrogen sulfide ions, HS −, at pH 14. UV–visible spectrophotometry was used to determine absorbances at 295 and 420 nm using an immersion probe, designed for highly corrosive environments. Three absorbance trends were found, corresponding to three concentration ranges of zero-valent sulfur: low (0–1.2 × 10 −3 mol dm −3 ), medium (1.2–3.6 × 10 −3 mol dm −3 ) and high (3.6–10 × 10 −3 mol dm −3 ). The non-linear dependence of absorbance on concentration over the range studied was due to disproportionation of polysulfides. Determination of these species is well known to be problematic at low concentrations due to the effects of adventitious oxygen in solution, meta-stability and speciation of polysulfide species: S2 2− – S8 2− . Oxygen concentrations must be minimised in the inert gas used to de-oxygenate sulfide solutions and for the same reason, their contact with atmospheric oxygen should be minimised. During potentiostatic oxidation of alkaline solutions containing HS − ions in the anolyte of electrochemical reactors incorporating cation-permeable membranes, temporal changes in anolyte absorbance and charge were used to estimate polysulfide concentrations. Charge yields for sulfide to polysulfide oxidation were close to unity, confirming the utility of the technique developed. Molar attenuation coefficients of the predominant polysulfide ions S3 2− at 420 nm and S4 2− at 295 nm were also estimated as 289 and 3609 dm 3 mol −1 cm −1, respectively, and comparable to values of (190, 206) and (3420, 3690) dm 3 mol −1 cm −1 reported previously.